Correlation between S100B and severity of depression in MDD: A meta-analysis. (3rd July 2022) - Tural, Umit; Irvin, Molly Kennedy; Iosifescu, Dan Vlad
Abstract: Background: Previous studies have demonstrated elevated levels of the S100B protein (located in glial cells) in major depressive disorder (MDD) as compared to healthy controls. However, studies reporting correlation between S100B levels and depression severity have been conflicting. Methods: We investigated, through systematic review and meta-analysis, whether the correlation between S100B levels and depression severity is significant in patients with MDD. Pearson correlation coefficients reported in the individual studies were converted to Fisher's Z scores, then pooled using the random effects model. Meta-regression was used to test modifiers of the effect size. Results: Sixteen studies including 658 patients with MDD met eligibility criteria. No publication bias was observed. There was a significant and positive correlation between serum S100B level and depression severity ( r = 0.204, z = 2.297, p = 0.022). A meta-regression determined that onset age of MDD and percentage of female participants are significant modifiers of this correlation. A moderate, but non-significant heterogeneity was observed in serum studies (44%). Conclusion: As many studies have reported significantly increased levels of S100B in MDD compared to controls, this meta-analysis supports the assumption that the increase in S100B correlates with the severity of MDD. Additional studies investigating the precise biological connection between S100B and MDD are indicated.